Series resistance effect on time zero dielectrics breakdown characteristics of MOSCAP with ultra-thin EOT high-k/metal gate stacks - 徐昊 杨红 王艳蓉 王文武 万光星 任尚清 罗维春 祁路伟 赵超 陈大鹏 刘新宇 叶甜春 (Journal of semiconductors, 2016)
The time zero dielectric breakdown characteristics of MOSCAP with ultra-thin EOT high-k metal gate stacks are studied. The TZDB results show an abnormal area dependence due to the series resistance effect. The series resistance components extracted from the Fowler-Nordheim tunneling relation are attributed to the spreading resistance due to the asymmetry electrodes. Based on a series model to eliminate the series resistance effect, an area acceleration dependence is obtained by correcting the TZDB results. The area dependence follows Poisson area scaling rules, which indicates that the mechanism of TZDB is the same as TDDB and could be considered as a trap generation process.